2017
DOI: 10.1016/j.ihj.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic features: Various atrial site pacing

Abstract: Atrial pacing is done for either symptomatic sinus node dysfunction (SND) or for maintenance of atrio-ventricular synchrony in a dual chamber pacemaker. Conventionally, atrial lead is placed in the right atrial appendage. Atrial conduction disorder in patients with permanent pacing results in higher incidence of atrial fibrillation. Atrial septal pacing has emerged as a solution to this problem. So, it is extremely important to understand the different features of paced P wave from various atrial pacing sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Harris et al also postulated the "dome and dart" morphology of the P wave in left atrial rhythm: the initial low-voltage, smooth component represents left atrial activation, and the high, sharp terminal component represents the right atrial activation. When the low atrial septum is paced, the P wave becomes negative in the inferior leads (II, III and avF) as the activation occurs in a caudo-cranial direction, and the P wave in lead V1 becomes positive as the left atrium is depolarized earlier than the right atrium [33].…”
Section: Discussionmentioning
confidence: 99%
“…Harris et al also postulated the "dome and dart" morphology of the P wave in left atrial rhythm: the initial low-voltage, smooth component represents left atrial activation, and the high, sharp terminal component represents the right atrial activation. When the low atrial septum is paced, the P wave becomes negative in the inferior leads (II, III and avF) as the activation occurs in a caudo-cranial direction, and the P wave in lead V1 becomes positive as the left atrium is depolarized earlier than the right atrium [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that RAA pacing changes the normal atrial pacing conduction sequence, increases the intra-atrial conduction time and makes the left and right atria asynchronous, which contributes to mitral valve regurgitation, increases the LA pressure and eventually leads to atrial structural and mechanical remodeling and an increased incidence of AF. 95,96 Therefore, scholars have proposed reducing burden of AF after pacemaker implantation by changing the atrial pacing site (Fig. 2).…”
Section: Changing the Pacing Sitementioning
confidence: 99%
“…Stylet-driven leads can be placed using a hand-modified J stylet or a deflectable stylet (Locator Plus, Abbott, Plymouth, MN, USA). 49 In normal-sized right atria a smaller radius J is ideal. In dilated right atria, a larger radius J stylet is used, and can be modified by bending the straight part of the stylet 1–1.5 cm before the start of the curve to 150°, which extends the reach.…”
Section: Bachmann’s Bundle Pacingmentioning
confidence: 99%